Theoretical Issues of Legal Regulation of Municipal Solid Waste Handling - Alua, Altynbekkyzy; Nurzhanovich, Bekezhanov Dauren (International Business and Accounting Research Journal, 2017)
The relevance of comparative analysis of legal regulation of environmental protection is due to several reasons. Firstly, it expands the boundaries of interpretation of legal norms and acts of environmental law. Secondly, it allows relying on experience in the latest achievements of legislative activity in developed countries. Thirdly, taking into consideration the legislative mistakes of other countries, it helps to avoid similar mistakes in the process of improving Kazakh legislation. And finally, it is the starting point for multilateral and bilateral cooperation in the field of environmental law.